The Effect of Oral Iron Supplementation/Fortification on the Gut Microbiota in Infancy: A Systematic Review and Meta-Analysis - Theoni Karamantziani; Abraham Pouliakis; Theodoros Xanthos; Konstantinos Ekmektzoglou; Styliani Paliatsiou; Rozeta Sokou; Nicoletta Iacovidou (MDPI AG, 2024)
(1) Background: Iron is an essential metal for the proper growth and neurodevelopment of infants. To prevent and treat iron deficiency, iron supplementation or fortification is often required. It has been shown, though, that it affects the synthesis of gut microbiota. (2) Methods: This paper is a systematic review and meta-analysis of the effect of oral iron supplementation/fortification on the gut microbiota in infancy. Studies in healthy neonates and infants who received per os iron with existing data on gut microbiota were included. Three databases were searched: PUBMED, Scopus, and Google Scholar. Randomized controlled trials (RCTs) were included. Quality appraisal was assessed using the ROB2Tool. (3) Results: A total of six RCTs met inclusion criteria for a systematic review, and four of them were included in the meta-analysis using both the fixed and random effects methods. Our results showed that there is very good heterogeneity in the iron group (I2 = 62%), and excellent heterogeneity in the non-iron group (I2 = 98%). According to the meta-analysis outcomes, there is a 10.3% (95% CI: −15.0-−5.55%) reduction in the bifidobacteria population in the iron group and a −2.96% reduction for the non-iron group. There is a confirmed difference (p = 0.02) in the aggregated outcomes between iron and non-iron supplement, indicative that the bifidobacteria population is reduced when iron supplementation is given (total reduction 6.37%, 95%CI: 10.16-25.8%). (4) Conclusions: The abundance of bifidobacteria decreases when iron supplementation or fortification is given to infants.